Turning Cannabis Into Cash: Agrarian Change and Lesotho’s Evolving Experience - Julian Bloomer (EchoGéo)
This article examines the evolving historical, geopolitical and economic context of cannabis cultivation in Lesotho. The article will present a brief history of cannabis cultivation in Lesotho, before assessing the possible impacts of recent changes in policy and legislation, following recent the announcement by the Lesotho government of production under license for companies cultivating medical cannabis. The article will conclude by critiquing the development potential of this recent move, against evolving policy debates in southern Africa.